The Covid-19 Exposure Risk to Nurses from Covid-19 Patients: A Descriptive Study - Nurfitri Nurfitri; Basri Basri; Nour Sriyanah; Andi Rizky Amaliah; Suradi Efendi; Muhammad Hatta (GLOBAL HEALTH SCIENCE GROUP, 2022)
Coronaviruses are a large family of viruses that cause illness ranging from mild to severe symptoms. The data on nurses who were infected with COVID-19 in the Camar room of the Dadi Hospital, South Sulawesi Province, Makassar City were 13 nurses. Objective: This study aims to describe the risk of exposure to the COVID-19 virus on nurses in the Camar Room at the Dadi Hospital, South Sulawesi Province, Makassar City. Method: This type of research is descriptive research. The sample of this research is nurses who treat COVID-19 patients as many as 51 respondents using the total sampling technique. Results: Based on a Nurse care activities have a very high risk of being exposed to COVID-19 as many as 51 respondents (100.0%), based on biological material accidents of nurses who do not experienced a biological material accident with a low risk of being exposed to COVID-19 as many as 45 respondents (88.2%) and those who experienced a high risk of exposure to biological material accidents as many as 6 respondents (11.8%) and based on bedience in carrying out the IPC, nurses who obedient the IPC at low risk of exposure to COVID-19 as many as 38 respondents (74.5%) and nurses who disobedient with the IPC at high risk of exposure to COVID-19 as many as 13 respondents (22.5 %). Conclusions: The conclusions of the study are those who have a high risk of being exposed to COVID-19 are respondents who carry out activities to care for COVID-19 patients and those who are at low risk of being exposed to COVID-19 are respondents who have not experienced biological material accidents as well as respondents who are bedient in carrying out IPC procedures. Suggestions for further researchers can develop further research on the description of the risk of exposure to COVID-19 in nurses.